2020
DOI: 10.1108/ecam-11-2019-0664
|View full text |Cite
|
Sign up to set email alerts
|

Understanding relationship between risks and claims for assessing risks with project data

Abstract: PurposeIn construction management, risks and claims are treated separately, but several studies tacitly acknowledge a strong link between the two. In this context, this research intends to investigate whether risks and claims have a causal relationship? Based on this causal relationship, a claim-based risk assessment model (C-RAM) is developed to quantify occurrences and cost implications of risks using project data.Design/methodology/approachFirst, the causal relationship between risks and claims is establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Kumar et al. (2021) highlighted the cost implications of a risk in a contract, mostly resulting in disputed claim.…”
Section: Avoiding Disputes: Leading Ppp To Desirable Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al. (2021) highlighted the cost implications of a risk in a contract, mostly resulting in disputed claim.…”
Section: Avoiding Disputes: Leading Ppp To Desirable Performancementioning
confidence: 99%
“…Consequently, the present study's credibility can be improved by using these high-quality literature reviews. Kumar et al (2021) highlighted the cost implications of a risk in a contract, mostly resulting in disputed claim. Akcay (2021) pointed out that the legal, contractor and operator risksas the ECAM 31,1 Dispute prevention strategies in PPP Cheung (2014) thematically groups construction dispute research into: conceptualization, avoidance and resolution, and strongly opines that equitable risk allocation and trust are well-known alternatives for avoidance strategies.…”
mentioning
confidence: 99%
“…There are many sources of risks in construction projects, especially in developing countries (Banaitiene and Banaitis, 2012; Kumar et al , 2020). Therefore, several studies were reviewed in the following section to collect risk factors and potential problems to suitably categorize them in order to serve the purpose of this study.…”
Section: Literaturementioning
confidence: 99%
“…However, Assaad and Abdul-Malak (2020) point out that the enforcement of penalty clauses as a legal remedy for contract breach, depends on the enforceability of lawswhether common, civil or Islamic lawunder which the contract is interpreted. Kumar et al (2020) have shown that if cost implications of a risk are not included in a contract, as a specific contractual clause, a claim will result. Thus, the risk category provisions (Khalef et al, 2021), extracted from previous studies, can be identified as follows: (1) change in work scope; (2) contractual documents' sufficiency; (3) liquidated damages (delay consequences); (4) consequential damages (indirect damages due to a breach);…”
Section: Introductionmentioning
confidence: 99%
“…However, Assaad and Abdul-Malak (2020) point out that the enforcement of penalty clauses as a legal remedy for contract breach, depends on the enforceability of laws – whether common, civil or Islamic law – under which the contract is interpreted. Kumar et al. (2020) have shown that if cost implications of a risk are not included in a contract, as a specific contractual clause, a claim will result.…”
Section: Introductionmentioning
confidence: 99%